Catharanthus roseus flower extract has wound-healing activity in Sprague Dawley rats - Pinto Pereira Lexley; Nayak BS (BMC, 2006)
Abstract Background Catharanthus roseus L (C. roseus) has been used to treat a wide assortment of diseases including diabetes. The objective of our study was to evaluate the antimicrobial and wound healing activity of the flower extract of Catharanthus in rats. Methods Wound healing activity was determined in rats, after administration (100 mg kg-1 day-1) of the ethanol extract of C. roseus flower, using excision, incision and dead space wounds models. The animals were divided into two groups of 6 each in all the models. In the excision model, group 1 animals were topically treated with carboxymethyl cellulose as placebo control and group 2 received topical application of the ethanol extract of C. roseus at a dose of 100 mg/kg body weight/day. In an incision and dead space model group 1 animals were given normal saline and group 2 received the extract orally at a dose of 100 mg kg-1 day-1. Healing was assessed by the rate of wound contraction, period of epithelization, tensile strength (skin breaking strength), granulation tissue weight, and hydoxyproline content. Antimicrobial activity of the flower extract against four microorganisms was also assessed Results The extract of C. roseus significantly increased the wound breaking strength in the incision wound model compared with controls (P < 0.001). The extract-treated wounds were found to epithelialize faster, and the rate of wound contraction was significantly increased in comparison to control wounds (P < 0.001), Wet and dry granulation tissue weights, and hydroxyproline content in a dead space wound model increased significantly (p < 0.05). Pseudomonas aeruginosa and Staphylococcus aureus demonstrated sensitivity to C. roseus Conclusion Increased wound contraction and tensile strength, augmented hydroxyproline content along with antimicrobial activity support the use of C. roseus in the topical management of wound healing.